Method of estimating elements of an interindustry matrix knowing row and column totals - Geary, R.C. (Economic & Social Studies, 1973)
It is a pity, but a fact of life, that few (if any) countries produce IO tables annually. The more common situation is that many countries produce these tables at intervals of years and then only with long delays. However, economic analysts cannot do without IO tables of reasonable up-to-dateness. Their position often is that they have a full IO table relating to five or six years ago, but (with reasonable accuracy from production statistics and national income accounts) only the marginal totals for more recent annual tables. These margins consist of gross output of agriculture (possibly in several divisions) and of industries and services, elements of final demand and of primary inputs for each such branch of economic activity.
Keywords: Interindustry matrix